2006
DOI: 10.1016/j.otohns.2005.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Internal Nasal Valve: Revisited with Objective Facts

Abstract: C-4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 9 publications
0
56
0
4
Order By: Relevance
“…The septal body is also located in the anterior nasal cavity, and contributes to the anatomy of the nasal valve. 4 Because of its contribution to nasal airflow, findings of compensatory septal body hypertrophy may also impact treatment for patients with nasal obstruction.…”
Section: Conclusion Discussionmentioning
confidence: 99%
“…The septal body is also located in the anterior nasal cavity, and contributes to the anatomy of the nasal valve. 4 Because of its contribution to nasal airflow, findings of compensatory septal body hypertrophy may also impact treatment for patients with nasal obstruction.…”
Section: Conclusion Discussionmentioning
confidence: 99%
“…[11] Currently there is no reliable examination method exists for the evaluation of the nasal respiratory function in the region of the nasal valve area where complex physiological correlations occur. [12] There have been a few important studies evaluating nasal valve area with acoustic rhinometry and CT. [6,8,13] In a more recent study, Cakmak et al [6] compared CT nasal valve area measurements with acoustic rhinometry and showed that a significant correlation between CT-derived cross-sectional areas obtained perpendicular to the acoustic axis and acoustic rhinometry.…”
Section: Discussionmentioning
confidence: 99%
“…La endoscopía nasal es un coadyuvante en el diagnóstico, de mucha utilidad en cirugía de revisión, para localizar adecuadamente zonas de sinequias posteriores y observar en forma dinámica aquellos sitios de colapso intranasal 11,[13][14][15] .…”
Section: Diagnósticounclassified